A Review of the Epidemiology of Temporal Lobe Epilepsy. (29th December 2011) - Téllez-Zenteno, Jose F.; Hernández-Ronquillo, Lizbeth
Abstract : Partial-onset epilepsies account for about 60% of all adult epilepsy cases, and temporal lobe epilepsy (TLE) is the most common type of partial epilepsy referred for epilepsy surgery and often refractory to antiepileptic drugs (AEDs). Little is known about the epidemiology of TLE, because it requires advanced neuroimaging, positive EEG, and appropriate clinical semiology to confirm the diagnosis. Moreover, recently recognized incidentally detected mesial temporal sclerosis in otherwise healthy individuals and benign temporal epilepsy indicate that the true epidemiology of TLE is underestimated. Our current knowledge on the epidemiology of TLE derives from data published from tertiary referral centers and/or inferred from population-based studies dealing with epilepsy. This article reviews the following aspects of the epidemiology of TLE: definitions, studies describing epidemiological rates, methodological observations, the interpretation of available studies, and recommendations for future studies.